Analisis Sensori dan Nilai Gizi Snack Bar Substitusi Tepung Ikan Teri (Stolephorus sp.) Sebagai Alternatif Makanan Selingan - Ulfatul Mardiyah; Siti Nur Aisyah Jamil; Abdul Muqsith; Siti Rodiyah (Samakia : Jurnal Ilmu Perikanan, 2022)
A snack bar is a type of snack made from various ingredients so that it can be used as a food diversification product. Anchovy flour has the potential to be used as an added ingredient for snack bars because it has the advantage of being consumed by all parts of the body. The purpose of this study was to determine consumer acceptance by organoleptic (hedonic) test as well as to determine the proximate content of snack bars substituted with anchovy flour. There are four formulations for making snack bars, including the addition of anchovy flour as much as 15% (P1), 25% (P2), and 35% (P3), and control (without the addition of anchovy flour). The results of organoleptic testing based on completely randomized design (CRD) and Duncan's follow-up test showed that the three treatments of adding anchovy were significantly different from the control for each test attribute (taste, aroma, color, and texture). Based on the mean value of each treatment with the addition of anchovy flour, it was known that P2 (addition of anchovy flour) has the highest level of preference of the panelists (attributes of taste, aroma, and texture). Proximate analysis on snack bar substitution of anchovy flour 15% (P2) obtained a water content of 8.27%, ash content of 11.06%, protein content of 18.63%, fat content of 15.44%, and carbohydrate content of 46.60%. Keywords: Snack Bar, Anchovy Flour, Organoleptic Test, Proximate Analysis.